The free and easy revolution. (New Statesman, 2006)
The article reports that 15 years after development began, the open-source operating system Linux is finally reaching its full potential. Linux was designed by thousands of computer geeks donating their time and efforts to create a free, downloadable operating system. It runs many commercial sites and is gaining popularity in the developing world.